1995
DOI: 10.1074/jbc.270.21.12725
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin 3 Is a Pentameric Molecule Held Together by Interchain Disulfide Linkage Involving Two Cysteine Residues

Abstract: The thrombospondins (TSPs) are a family of 5 distinct gene products designated TSP1, -2, -3, -4, and COMP, for cartilage oligomeric matrix protein. TSP1, the prototypical member, is a trimeric extracellular matrix molecule implicated in cell migration and development. TSP1 trimer formation is mediated by interchain disulfide linkage involving two NH2-terminal cysteines. TSP3, a recent addition to the family, is a developmentally regulated heparin binding protein that is similar in sequence to the COOH terminus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 24 publications
3
37
1
Order By: Relevance
“…Rotary shadowing has demonstrated that, in the presence of Ca 2ϩ , a globule composed of the C-terminal portion of TSP1 enlarges while the stalk connecting the oligomerization domain to the C-terminal globule shortens (13)(14)(15). This structural change was also observed for TSP3 (16), TSP4 (17), and TSP5/COMP (18). The structure of TSP2 is also Ca 2ϩ -sensitive based on its susceptibility to trypsin proteolysis (19).…”
mentioning
confidence: 91%
“…Rotary shadowing has demonstrated that, in the presence of Ca 2ϩ , a globule composed of the C-terminal portion of TSP1 enlarges while the stalk connecting the oligomerization domain to the C-terminal globule shortens (13)(14)(15). This structural change was also observed for TSP3 (16), TSP4 (17), and TSP5/COMP (18). The structure of TSP2 is also Ca 2ϩ -sensitive based on its susceptibility to trypsin proteolysis (19).…”
mentioning
confidence: 91%
“…Although the close apposition and head-to-head orientation of Mtx and Thbs3 raise the possibility that the two genes share a bidirectional promoter, several lines of evidence suggest that these genes are regulated independently. First, Mtx mRNA is ubiquitously distributed in the mouse, whereas Thbs3 mRNA is restricted to lung, cartilage, the gastrointestinal tract, and hippocampus (2,8,9). Secondly, the basal elements of the Mtx and Thbs3 promoters can largely be dissociated, which indicates that the Mtx and Thbs3 genes are not regulated by a true bidirectional promoter (7).…”
mentioning
confidence: 99%
“…Pentameric TSPs, including TSP3, form ␣-helical coiled-coil domains in which the axial channel or pore is lined by hydrophobic amino acids (12,22,24). In the case of TSP5/COMP this axial pore is capable of binding physiologically relevant hydrophobic molecules such as vitamin D and all-trans retinol with appropriate affinities (14), and this property is likely to extend to TSP3.…”
mentioning
confidence: 99%
“…However, the specificity of the antibody that was used in this study is questionable, since in another study it stained all tissues in some sections indiscriminantly (26). In the chicken, TSP3 mRNA was expressed in embryonic cartilage and in neurons that are actively extending processes (28), and in Xenopus embryos TSP3 mRNA was detected in the notocord, floor plate, sensorial layer of the ectoderm, and sensory epithelia (30).Pentameric TSPs, including TSP3, form ␣-helical coiled-coil domains in which the axial channel or pore is lined by hydrophobic amino acids (12,22,24). In the case of TSP5/COMP this axial pore is capable of binding physiologically relevant hydrophobic molecules such as vitamin D and all-trans retinol with appropriate affinities (14), and this property is likely to extend to TSP3.…”
mentioning
confidence: 99%